Pengaruh Pendelegasian Wewenang Dan Kemampuan Kerja Terhadap Kinerja Pegawai Pada Kantor Pemerintahan Kecamatan Tapian Nauli Kabupaten Tapanuli Tengah - Fabio Cannavaro Hutagalung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine whether there is an effect of delegation of authority and work ability on employee performance at the Tapian Nauli District Government Office, Central Tapanuli Regency. The sample in this study consisted of 34 employees of the Tapian Nauli District Government Office. The data analysis technique used was Multiple Linear Regression. The results of multiple linear regression analysis obtained the equation Y = 7.389 + 0.453X1 + 0.350X2. The constant value of 7.389 indicates that if delegation of authority (X1) and work ability (X2) are equal to 0, then employee performance (Y) is 7.389, and if X1 and X2 are equal to 1, then employee performance becomes 8.192. Based on the t-test results, delegation of authority has a t-value of 2.505 > t-table 1.69552 with a significance value of 0.018 < 0.05, indicating a significant effect on employee performance. Work ability has a t-value of 2.632 > t-table 1.69552 with a significance value of 0.013 < 0.05, indicating a significant effect on employee performance. Based on the F-test, the F-value is 11.091 > F-table 3.305, which means that delegation of authority and work ability simultaneously have a positive and significant effect on employee performance at the Tapian Nauli District Government Office, Central Tapanuli Regency.